There's a duwende in my brother's soup (May dewende sa sopas ng kapatid ko!) - Saguisag, Lara; Nada, Marcus; Garlitos, Rhandee; Rivera, Augie (Quezon City Lampara Publishing House, Inc., 2001)
"Lara Saguisag brings to us a heartwarming story about Ginny's search for his brother's mysterious playmate which she believes is an elf! This takes her to an amazing discovery of the world of autism... There's a Duwende in my Brother's Soup! is the first Filipino children's story that helps develop a greater understanding, awareness, and acceptance of children with autism."
Text in English and Filipino.
Keywords: Autism in children -- Fiction; Autism -- Fiction